Alloantibodies in previously untreated hemophilia A patients: the role of environmental factors. (1st July 2013) - Franchini, Massimo; Frattini, Francesco; Crestani, Silvia; Bonfanti, Carlo
<x xml:space="preserve">Abstract</x> The therapy of hemophilia A has nowadays reached a high degree of quality, being probably the most efficacious and safe treatment available among other monogenic disorders. In this context, the most challenging complication of therapy has become the development of inhibitory alloantibodies against FVIII. These inhibitors, which develop in up to 30% of severe hemophilia A patients, render replacement therapies ineffective, limit patient access to a safe and effective standard of care, and predispose them to an increased risk of morbidity and mortality. Several possible risk factors, both genetic and environmental, for inhibitor development have been identified in previously untreated patients, confirming that the etiology of this phenomenon is multifactorial. In this narrative review, we will focus on acquired risk factors, discussing the pathogenic and clinical data available from the literature analysis.